Birds as reservoirs for Borrelia burgdorferi s.l. in Western Europe: circulation of B. turdi and other genospecies in bird-tick cycles in Portugal - Norte, A.C. (2012)
Birds as reservoirs for Borrelia burgdorferi s.l. in Western Europe: circulation of B. turdi and other genospecies in bird-tick cycles in Portugal. Norte AC, Ramos JA, Gern L, Núncio MS, Lopes de Carvalho I. SourceInstitute of Marine Research IMAR/CMA, Department of Life Sciences, University of Coimbra, Apartado 3046, 3001-401 Coimbra, Portugal. Center for Vector and Infectious Diseases Research, National Health Institute Doutor Ricardo Jorge, Lisbon, Portugal. Laboratory of Eco-Epidemiology of Parasites, Institute of Biology, University of Neuchâtel, Neuchâtel, Switzerland. Abstract Birds are important in the ecology of Borrelia burgdorferi sensu lato (s.l.) because they are important hosts for vector tick immature stages and are known reservoirs for some Borrelia genospecies. The aim of our study was to assess the role of common passerine bird species as reservoirs for B. burgdorferi s.l. in Western Europe. We surveyed birds in enzootic areas in Portugal, where no information is available for birds as reservoirs for this aetiologic agent and where B. lusitaniae, for which few reservoirs have been identified, is the dominant genospecies. Twenty-three birds (2.9%), including Turdus merula, T. philomelos, Parus major and Fringilla coelebs harboured infected ticks, but only Turdus sp. harboured infected tick larvae. In one study area, although B. lusitaniae was dominant in questing Ixodes ricinus, no ticks feeding on birds were infected with this genospecies, and B. valaisiana was the dominant genospecies in I. ricinus larvae feeding on birds. In the other area ticks collected from birds were mainly I. frontalis which were infected with B. turdi. Two skin biopsies (4.2%) from two T. merula were positive, one for B. valaisiana and the other for B. turdi. This is the first report for B. turdi in Western Europe. © 2012 Society for Applied Microbiology and Blackwell Publishing Ltd. PMID:22882497[PubMed - as supplied by publisher]